PEMBENTUKAN KEBIJAKAN PARTISIPATIF DALAM PERSPEKTIF PEMERINTAHAN KOLABORATIF DI KABUPATEN SAMBAS PROVINSI KALIMANTAN BARAT - Willy Mulyadi (Program Magister Ilmu Politik, Universitas Diponegoro, 2017)
Convensional model of public policy makings in Sambas district, West Borneo Province, so far rely more on the strength of institutional structures and elites with less open processes. The impact in many case of planning has failed to identify and accommodate governance issues. This research uses qualitative explorative methods which are assisted with soft system methodology as suggester by Checkland (1999). Analysis of research uses collaborative governance theory in looking at the process of preparation of regional medium term development plan (RPJMD) of 2016-2021. Result of this research illustrates that the failure in the preparation of planning for this is caused by access to stakeholder involvement that is limited, the role of the government is very dominant so that RPJMD is not considered as a shared commitment and responsibility, the implication of each party working independently in accordance with their respective interest. It is also apparent that the process of preparing planning has not been sufficient to meet accessability and drivers in the form of citizen's education and lack of seriousness in the implementation of bureaucratic reform to become an implementative reference for the formation of participatory policy making according to the perspective of collaborative governance in regions with similar characteristics.